Peer Support Workers in Health: A Qualitative Metasynthesis of Their Experiences. - Jennifer MacLellan; Julian Surey; Ibrahim Abubakar; Helen R Stagg (PLoS ONE)
Objective Peer support models, where an individual has a specific illness or lifestyle experience and supports others experiencing similar challenges, have frequently been used in different fields of healthcare to successfully engage hard-to-reach groups. Despite recognition of their value, the impact of these roles on the peer has not been systematically assessed. By synthesising the qualitative literature we sought to review such an impact, providing a foundation for designing future clinical peer models. Methods Systematic review and qualitative metasynthesis of studies found in Medline, CINAHL or Scopus documenting peer worker experiences. Results 1,528 papers were found, with 34 meeting the criteria of this study. Findings were synthesised to reveal core constructs of reframing identity through reciprocal relations and the therapeutic use of self, enhancing responsibility. Conclusions The ability of the Peer Support Worker to actively engage with other marginalised or excluded individuals based on their unique insight into their own experience supports a therapeutic model of care based on appropriately sharing their story. Our findings have key implications for maximising the effectiveness of Peer Support Workers and in contributing their perspective to the development of a therapeutic model of care.